2021
DOI: 10.1371/journal.pone.0258358
|View full text |Cite
|
Sign up to set email alerts
|

Starting parenting in isolation a qualitative user-initiated study of parents’ experiences with hospitalization in Neonatal Intensive Care units during the COVID-19 pandemic

Abstract: Background Worldwide, strict infection control measures including visitation regulations were implemented due to the COVID-19 pandemic at Neonatal Intensive Care Units (NICUs). These regulations gave restricted access for parents to their hospitalized infants. The consequence was limited ability to involve in the care of their infants. At Oslo University Hospital entry to NICU was denied to all except healthy mothers in March 2020. The absolute access ban for fathers lasted for 10 weeks. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…In our study, participants highlighted greater impact on three patient groups: older children in ICU who were awake and unaccompanied, children receiving palliative care and neonates. There is now a body of published evidence to support these findings related to children’s intensive care24 and neonatal intensive care,25–28 where parents echoed the views of our participants citing the isolation of being the parent in the hospital or at home during an admission. The rapid introduction of restrictions and the slow and uneven return to parental and family-centred care have implications for longer term impact on families as well as staff who provided care during these restrictions.…”
Section: Discussionmentioning
confidence: 53%
“…In our study, participants highlighted greater impact on three patient groups: older children in ICU who were awake and unaccompanied, children receiving palliative care and neonates. There is now a body of published evidence to support these findings related to children’s intensive care24 and neonatal intensive care,25–28 where parents echoed the views of our participants citing the isolation of being the parent in the hospital or at home during an admission. The rapid introduction of restrictions and the slow and uneven return to parental and family-centred care have implications for longer term impact on families as well as staff who provided care during these restrictions.…”
Section: Discussionmentioning
confidence: 53%
“…Parents in our survey reported higher feelings of trauma from being alone without a support person across situations encountered in the NICU. A recent qualitative study found that the restriction of fathers’ access to the NICU significantly impacted early infant–father bonding and led to feelings of isolation and loneliness by the mothers ( Kynø et al, 2021 ). These findings are consistent with a review of the literature examining the safety of maintaining family-integrated care in NICUs during the COVID-19 pandemic and recommendations for care ( van Veenendaal et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Parents of NICU babies have high expectations of healthcare professionals ( Duran et al, 2020 ; Kynø et al, 2021 ; Musabirema et al, 2015 ). Our participants wanted to FaceTime with their babies more often.…”
Section: Discussionmentioning
confidence: 99%